The law and policy of financial regulation and deregulation of Nigerian banking system - Adeeko, Olukayode Adesope (1998)
This thesis is a study of banking regulation in Nigeria. It has three main objectives: to explain the evolution and impact of banking regulation after independence to discuss the reasons for the persistent failure of financial regulation; and to highlight the role of external agencies in Nigeria's financial system. The thesis offers a historical perspective on the developments in Nigerian banking regulation, but focuses mainly on the period after independence. It examines the economic and political theories that have influenced financial regulatory trends in Nigeria. It considers these theories in their political and legal context. The thesis does not embrace any theory in particular. Instead, its approach is pragmatic and comparative focusing on the interaction between legal, political and institutional factors that have influenced financial regulation in Nigeria. The study shows that the pre-liberalisation regulatory norms were repressive and inefficient. It argues that banking deregulation was introduced as an economic revolution devoid of necessary corresponding political and legal changes. The core destabilising factors are identified as inadequate regulatory powers, political corruption, political instability, legal instability, policy distortions, and incongruous laws. The complicity of the IMF and World Bank in this process is also discussed. Financial deregulation was prompted by predatory politics characteristic of the Nigerian state; yet, deregulation has aggravated the country's political instability and exacerbated prebendalism. The thesis discusses policy options to break this vicious circle.